Wujud dan Pola Penalaran Nilai Kepedulian, Kreatif, dan Sopan Santun Materi Ajar Bahasa Indonesia dalam Buku Siswa Kelas VII Kurikulum 2013 - Handayani, Liza Tri, Laili Etika Rahmawati, S.Pd; M.Pd (2016)
Character of the nation the last few years to be degraded. Factually, the data showed that the morality or character of the nation has now collapsed. Character ed ucation through the learning process. In addition to the learning process, it turns out the learning material too. Many times in the textbook contains learning materials to the value of the attitude that must be followed. The purpose of this study to descr ibe the nature and patterns of reasoning values of caring, creative, and manners Indonesian learning materials in class VII curriculum 2013. This research use descriptive eksplanatif. Data of this study is learning materials of text containing the value of caring, creative, and manners. Data were analyzed using data analysis techniques flow model of Miles and Huberman. The results showed that there were 27 form values of caring, 11 creative values, and 6 manners values in Indonesian learning materials in books class VII curriculum 2013. It was also the pattern of reasoning appropriate at this stage of the scientific approach. The pattern of reasoning realized that the process of deductive reasoning, analogy inductive, deductive analogy, the relationship causal-effect, relationship effect-causal, and causal-effect 1- second effect. The new pattern appears that the causal relation ship 1-second effect-effect 3, and causal relationship-effects.